The Level of Well-being and Mental Health Symptoms Among Student-Athletes Across a COVID-19 Affected Academic Year - JOANNE CHRISMAS (2022)
Background information: Due to their dual-career lifestyles, the student-athlete population can be at-risk of lowered well-being and mental ill-health. Furthermore, the novel coronavirus disease (COVID-19) pandemic has raised additional threats to student-athletes' well-being and mental health. Despite this, student-athletes appear reluctant to seek support for any well-being or mental health concerns they may have. Thus, this study aimed to identify the levels of well-being and psychological distress in United Kingdom (UK) student-athletes, alongside ascertaining COVID-19's effects on well-being and the level of help-seeking behaviour. Method: A total of 277 high-performance student-athletes from a UK-based university completed an online survey at two time-points during an academic year to measure the levels of well-being, psychological distress, self-stigma, and help-seeking behaviours. The survey was distributed via emails to the Performance Directors' and included questions on background information, the self-perceived effect of COVID-19 on well-being, WEMWBS and K10 scales. Results: The student-athlete participants, on average, reported medium levels of well-being, with medium to high psychological distress across the academic year. COVID-19 reduced self-perceived well-being for 39.4% of participants, primarily due to the loss of training and competition. An independent t-test identified males held significantly lower psychological distress than females (p = .002) at time-point 1. There were no gender differences in help-seeking behaviours (p > .05). Multiple regression models showed gender, time-point, self-stigma, sport, and help-seeking intentions significantly contributed to well-being and psychological distress. Conclusion: Across the academic year of 2020/21, performance student-athletes' well-being and mental health lowered, likely due to several factors that included the COVID-19 pandemic and help-seeking behaviours. More research is needed to understand the impact of well-being and mental health on student-athletes within the UK, the long-term impact of the COVID-19 pandemic, and factors that affect help-seeking behaviour.